The Use of Scaffolding Strategies with Beginning English as a Foreign Language (EFL) Learners to Enhance Speaking and Reading Abilities in a Conversational English Course - Barboza Jiménez , Kendall (2026)
Beginning English as a Foreign Language (EFL) studens often encounter challenges that require teachers to implement a variety of strategies to support their language development. Scaffolding has been documented across educational settings as a valuable approach for assisting learners; therefore, this study aims to examine beginning EFL students’ perceptions of scaffolding in the development of reading and speaking skills and to offer recommendations for teachers working with novice learners. This qualitative case study was conducted in a conversational English course offered through an outreach project at a public university in Corredores, Costa Rica. The data collection process included two structured observations, two focus groups, and one semi-structured interview. Sixteen students and one student-teacher participated in the structured observations. The focus groups were conducted with eight beginner EFL students (four male and four female) ages 16 to 18 years old. The semi-structured interview was conducted with the student-teacher. The data revealed several challenges faced by the learners, as well as the scaffolding strategies the teacher implemented to address these difficulties. Learners expressed positive perceptions of the use of scaffolding in their language-learning process and, along with the student-teacher, provided recommendations for EFL teachers on its effective use. Based on the findings, from a learner perspectives, scaffolding is an effective approach for improving reading and speaking abilities and for addressing linguistic challenges. Recommendations encompass encouraging EFL learners to maintain openness to scaffolding strategies; ensuring that educators consider learners needs, preferences, and difficulties; cultivating a positive and supportive learning atmosphere; and delivering constructive and considerate feedback. This study underscores the importance of scaffolding in initial EFL classrooms and proposes that its implementation can be enhanced through an action plan, such as a teacher workshop, designed to facilitate the integration of scaffolding strategies for the advancement of reading and speaking skills.